Pelindungan Hukum Hak Cipta terhadap Lagu Halo-Halo Bandung yang Diubah Menjadi Hello Kuala Lumpur - Zahra, Salya Afina Aulia; Mayana, Ranti Fauza; Permata, Rika Ratna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of information and communication technology has caused world relations to become borderless. This can be seen on the creation of a song that can easily be transformed into a new song and uploaded on a digital platform without the permission of the Copyright Holder of the changed song, as well as the legal acts committed by foreign nationals outside the territory of Indonesia, such as one of the cases that the author researched, involving the national song Halo-Halo Bandung, which allegedly was transformed into a song titled Hello Kuala Lumpur without permission and uploaded on a Malaysian YouTube account named Lagu Kanak TV. The purpose of this research is to determine and analyze the legal provisions that can be imposed on the Hello Kuala Lumpur song maker or the owner of the Lagu Kanak TV YouTube account and also to find out the legal actions that can be taken by the Heirs of the Creator and the Copyright Holder of the song Halo-Halo Bandung and the Indonesian Government. The research method used in this research is normative juridical, which is legal research that bases its study on legal regulations. There is an examination of legal documents related to this research topic. The data collection technique used is a literature study by reviewing the relevant literature and legal regulations. Based on the results of the research, it is known that the act of changing the song Halo-Halo Bandung into Hello Kuala Lumpur by Lagu Kanak TV and its broadcast through YouTube without permission is a form of Copyright infringement on moral rights and economic rights. Dispute resolution through negotiation is recommended for both parties because negotiation is an effective way of resolving disputes and has several advantages.